Synthesis, Spectroscopic and Biological Activities Of Complexes Of 2-[(3-Chlorobenzylidene) Hydrazinylidene]-1,2-Diphenylethanimine - Sankhe, Sharad; Shah, Krupali (International Journal of Membrane Science and Technology, 2023)
This study provides the synthesis of the mononuclear complexes of 2-[(3-Chlorobenzylidene)hydrazinylidene]-1,2-diphenylethanimine ligand (HBMHmCB). We have used elemental, spectral, X-ray, and magnetic moment investigations to characterize all of the compounds. Oximino ions have monodentate coordinated with the metal ions, according to the infrared spectra. This coordination takes place at the O2N2Cl2 donor sites of deprotonated oximino single bond OH, as well as at the imine N atoms of hydrazone and aromatic chloro group. Octahedral geometry is shown by spectroscopic and magnetic investigations of the Ni(II), Fe(II), Co(II), Mn(II), and Cu(II) complexes. While complexes with Zn(II), Hg(II), and Cd(II) exhibit tetrahedral geometry, Pd(II) possesses square planar geometry. The antimicrobial and cytotoxic properties of freshly synthesized compounds were studied. The complexes are effective against a wide variety of bacteria and yeasts, including C. albicans, S. cerevisiae, B. subtilis, P. aeruginosa, and E. coli. The HBMHmCB ligand and its complexes exhibited a wide range of cytotoxic properties.